Into the revolution of generative artificial intelligence to develop seasonal fashion mood boards - Jannat Rakeya; Ashif Akash B.M.; Islam Nahid-Ull (Tekstilna industrija, 2025)
There is a growing interest in using generative artificial intelligence (GAI) tools in the fashion industry. Even though there is a research gap on the possibilities of new AI image-generation tools for mood board design, this study evaluates the efficiency of one such GAI tool, Dream Lab AI, in mood board development. Three steps were required to conduct the research: transforming an initial notion into clear textual design prompts, utilizing generative artificial intelligence technologies to facilitate concept creation, and validating the resulting mood indicate through analysis using mood board principles. The outcomes show how successful Dream Lab AI is and show that by fully utilizing the controllability of various mood board design concepts, this tool can speed up the design process for designers. Dream Lab AI has the potential to reduce time, labour, and cost as well as facilitating a sustainable approach in mood board fashion design process. The study observes that inadequate data training and prompt accuracy of GAI in using mood board design may have an impact on the feasibility of the mood board designs produced and that designs may not be compatible with real-world mood board design. The study suggests better proper data training and interactive prompt implementation in AI tools can help the designer to develop mood boards effectively.